Effect of storage time on fatty acid composition of subcutaneous fat - Pedro E. de; Murillo M. (Tradition and innovation in Mediterranean pig production, 2000)
Samples of subcutaneous fat from 10 Iberian pigs were kept at -20 degrees C for 32 months. The samples were analysed, using gas chromatography, at 0, 6, 12 and 32 months and the composition in fatty acids was obtained. The variance analysis shows the similarities between the fatty acid composition along the 32 months. Small significant differences (P less than 0.01) were obtained for C18:0 after 6 and 12 months as compared to the initial month. However, those small differences could be due to a change in the chromatographic column and in the injection method (automatic versus manual) during the assay period. Furthermore, no significant differences were found between the composition in C18:0 at 32 months as compared to the zero month.
4. International Symposium on Mediterranean Pig, 1998/11/26-28, Evora (Portugal)